Enhancing Student Vocabulary Mastery By Using Kinesthethic Method at SDN Nagaleah - Jami, Sonia Vriska Yulinda; Norahmi, Maida; Pratika, Dellis; Muliawan, Sunanda Alam; Nasution, Hikmal Maulana (Bhinneka Publishing, 2025)
This community service program explored the use of the kinesthetic method to enhance children’s English vocabulary through the Engage, Study, and Activate (ESA) approach. The program was carried out with 12 sixth-grade students at SDN Nagaleah, Barito Timur, over three interactive learning sessions that focused on vocabulary related to animals and body parts. The teaching process integrated games, songs, gestures, and visual aids to create an engaging and enjoyable learning environment for the children. To measure the effectiveness of the activities, a pre-test and post-test were administered, and the results showed a significant improvement in students’ vocabulary mastery, with the average score rising from 69.17 to 91.25, representing a 31.93% enhancement. These outcomes highlight that community service activities in education can effectively support children’s vocabulary acquisition by encouraging active participation, improving memory retention, and fostering motivation to learn.